Prevalence and predictors of anxiety and depression among esophageal cancer patients prior to surgery. Issue 8 (6th November 2015) - Hellstadius, Y.; Lagergren, J.; Zylstra, J.; Gossage, J.; Davies, A.; Hultman, C. M; Lagergren, P.; Wikman, A.
Summary: This study aims to establish the prevalence and predictors of anxiety and depression among esophageal cancer patients, post‐diagnosis but prior to curatively intended surgery. This was a cross‐sectional study using data from a hospital‐based prospective cohort study, carried out at St Thomas' Hospital, London. Potential predictor variables were retrieved from medical charts and self‐report questionnaires. Anxiety and depression were measured prior to esophageal cancer surgery, using the Hospital Anxiety and Depression Scale. Prevalence of anxiety and depression was calculated using the established cutoff (scores ≥8 on each subscale) indicating cases of 'possible‐probable' anxiety or depression, and multivariable logistic regression analyses were performed to examine predictors of emotional distress. Among the 106 included patients, 36 (34%) scored above the cutoff (≥8) for anxiety and 24 (23%) for depression. Women were more likely to report anxiety than men (odds ratio 4.04, 95% confidence interval 1.45–11.16), and patients reporting limitations in their activity status had more than five times greater odds of reporting depression (odds ratio 6.07, 95% confidence interval 1.53–24.10). A substantial proportion of esophageal cancer patients report anxiety and/or depression prior to surgery, particularly women and those with limited activity status, which highlights a need for qualified emotional support.